Biblical Thomism: What is Next? - Vijgen, Jörgen (Biblica et Patristica Thoruniensia, 2018)
Tomizm biblijny. Co dalej? Recenzja książki: Michael O’Connor, Cajetan’s Biblical Commentaries. Motive and Method, Brill, Leiden, 2017, xvi + 302 ss. ISBN: 978-04-32506-7